PD-1 does not mark tumor-infiltrating CD8+ T cell dysfunction in human gastric cancer - Ying Wang; Lina Wang; Yuan Zhuang; Yipin Lv; Yongliang Zhao; Fangyuan Mao; Yongsheng Teng; Liusheng Peng; Ping Cheng; Weisan Chen; Quanming Zou; Yang Shen; et al. (Journal for ImmunoTherapy of Cancer)
Background Overexpression of programmed cell death protein 1 (PD-1) is linked to CD8+ T cell dysfunction and contributes to tumor immune escape. However, the prevalence and functional regulations of PD-1 expression on CD8+ T cells in human gastric cancer (GC) remain largely unknown.Methods Flow cytometry was performed to analyze the level, phenotype, functional and clinical relevance of PD-1+CD8+ T cells in GC patients. Peripheral blood CD8+ T cells were purified and subsequently exposed to culture supernatants from digested primary GC tumor tissues (TSN) in vitro for PD-1 expression and functional assays. Tumor responses to adoptively transferred TSN-stimulated CD8+ T cells or to the TSN-stimulated CD8+ T cell transfer combined with an anti-PD-1 antibody injection were measured in an in vivo xenograft mouse model.Results GC patients’ tumors showed a significantly increased PD-1+CD8+ T cell infiltration. However, these GC-infiltrating PD-1+CD8+ T cells showed equivalent function to their PD-1−CD8+ counterparts and they did not predict tumor progression. High level of transforming growth factor-β1 (TGF-β1) in tumors was positively correlated with PD-1+CD8+ T cell infiltration, and in vitro GC-derived TGF-β1 induced PD-1 expression on CD8+ T cells via Smad3 signaling, whereas Smad2 signaling was involved in GC-derived TGF-β1-mediated CD8+ T cell dysfunction. Furthermore, GC-derived TGF-β1-mediated CD8+ T cell dysfunction contributed to tumor growth in vivo that could not be attenuated by PD-1 blockade.Conclusions Our data highlight that GC-derived TGF-β1 promotes PD-1 independent CD8+ T cell dysfunction. Therefore, restoring CD8+ T cell function by a combinational PD-1 and TGF-β1 blockade might benefit future GC immunotherapy.